One-Pot Transition-Metal-Free Synthesis of Weinreb Amides Directly from Carboxylic Acids - Niu, Teng; Wang, Ke-Hu; Huang, Danfeng; Xu, Changming; Su, Yingpeng; Hu, Yulai; Fu, Ying (Synthesis, 2014)
Weinreb amides were prepared directly from carboxylic acids, N,O-dimethylhydroxylamine, and phosphorus trichloride in one pot at 60 °C in toluene in high yields, thus avoiding the separation of the moisture and air sensitive intermediate P[NMe(OMe)]3 in advance. Sterically hindered carboxylic acids also give the corresponding Weinreb amides in excellent yields. Various functional groups are tolerated on the carboxylic acid. The method, which is a simple process and gives high yields, is suitable for large-scale production.
Keywords: Weinreb amides; carboxylic acids; one-pot reaction; coupling; synthesis